Daisy Hontiveros Avellana first lady of Philippine theater - Marasigan, Dennis; Adlawan, Irma; Avellana, Jose Mari; De la Cruz, Libertine Santos (Kuwadro., 2002)
Documents Daisy Hontiveros Avellana's efforts as actor, director, producer and writer. She was a recipient of numerous prizes, honors and awards, including Gawad Siglo ng Aliw, Tandang Sora Award for Theater, the Patnubay ng Sining at Kalinangan Award, Gintong Ina Award for Theater, Gawad CCP Para sa Sining and the CCP Centennial Honors for the Arts.